Effect of the Large and Small T-Antigens of Human Polyomaviruses on Signaling Pathways - Moens, Ugo (Int J Mol Sci, 2019)
Viruses are intracellular parasites that require a permissive host cell to express the viral genome and to produce new progeny virus particles. However, not all viral infections are productive and some viruses can induce carcinogenesis. Irrespective of the type of infection (productive or neoplastic), viruses hijack the host cell machinery to permit optimal viral replication or to transform the infected cell into a tumor cell. One mechanism viruses employ to reprogram the host cell is through interference with signaling pathways. Polyomaviruses are naked, double-stranded DNA viruses whose genome encodes the regulatory proteins large T-antigen and small t-antigen, and structural proteins that form the capsid. The large T-antigens and small t-antigens can interfere with several host signaling pathways. In this case, we review the interplay between the large T-antigens and small t-antigens with host signaling pathways and the biological consequences of these interactions.